Determinan yang Mempengaruhi Keikutsertaan Pasangan Suami Istri dalam Mengikuti Tes HIV Selama Masa Kehamilan (Journal of Telenursing (JOTING), 2024)
This study aims to determine whether employment, education and family income are related to the participation of married couples in taking HIV tests during pregnancy. The method used was a quantitative study with a cross sectional research design. The results of this study show that there are still many couples who do not test for HIV during pregnancy and husbands are the largest number of subjects who do not test for HIV. In conclusion, only educational characteristics are related to the wife's participation in HIV testing during pregnancy Keywords: HIV Test, Married Couple, Pregnancy.